ENHANCING CIVIL SERVICE COMPETENCEA COMPARATIVE STUDY OF QUALITY CONTROL INSPECTOR STANDARDS IN INDONESIA AND THAILAND - Nadia Bella Anggraini (Universitas Diponegoro, 2025)
This study examines and compares the competency standards of quality control inspectors in Indonesia and Thailand, with the aim of improving the effectiveness of public services. This study discusses the challenges faced by civil servants in meeting competency expectations and examines the regulatory framework that guides these standards. Using a qualitative comparative design, data were collected through document analysis and semi-structured interviews with 20 participants in both countries. These findings reveal significant differences: Indonesia emphasizes technical competence in accordance with PAN RB Ministerial Regulation No. 38 of 2017, while Thailand focuses on compliance with regulations outlined by the Ministry of Trade. Despite this framework, both countries face implementation gaps, especially in Indonesia, where inspectors often experience role ambiguity and training limitations. In contrast, Thailand has implemented a clearer competency framework as well as a comprehensive training program that has improved the consistency of service quality and public trust. The study concludes that establishing a clear and context-specific competency framework, along with a comprehensive training program, is crucial for enhancing inspector effectiveness. Recommendations include regular evaluation of standards and encourage collaboration between stakeholders to support sustainable competency development. The study provides valuable insights into public administration, highlighting the importance of well-equipped civil servants in delivering high-quality public services.